Comparative evaluation of blood contamination on the push-out bond strength of mineral trioxide aggregate, Biodentine, and bone cement in furcation perforation repair: An in vitro study - Swapnika Gudapati; R. Kalyan Satish; Girija S. Sajjan; K. Madhu Varma; V. Santosh Kumar (Endodontology)
Aim: This in vitro study was designed to compare the effect of blood contamination on the push-out bond strength of mineral trioxide aggregate (MTA), Biodentine, and bone cement. Methods: Seventy-eight human mandibular molars with furcation were selected and decoronated at the cementoenamel junction. The samples were mounted 3 mm below the furcation area into the acrylic resin. A perforation in the center of the furcation was made using a round carbide bur size 3 with a diameter of 1.2 mm. Then, the perforation was enlarged up to a standardized diameter of 1.3 mm using a size 5 Gates-Glidden drill. The samples were randomly divided into three groups. Based on blood contamination status, each group (n = 26) was further subdivided into two subgroups (n = 13). Whole fresh human blood was obtained from the principal investigator of the research group. A 27-gauge syringe was used to inject blood into the perforated furcal area. A piece of gelatin was packed under the furcal area using a condenser. MTA, Biodentine, and bone cement were mixed according to the manufacturer’s recommendations and compacted into the perforation. A universal testing machine was used to evaluate the push-out bond strength. The results were analyzed using one-way analysis of variance followed by Tukey’s post hoc test (P < 0.05). Results: In the experimental groups with blood contamination, Group 2A exhibited statistically significant push-out bond strength values compared with Group 1A and Group 3A. In the groups without blood contamination, Group 2B showed statistically significant push-out bond strength values compared with Group 1B and Group 3B. Irrespective of the blood contamination status, Group 3 exhibited higher push-out bond strength values than Group 1, with no statistically significant difference between the groups. No significant difference was observed within the groups. Conclusion: Biodentine showed promising results as a better perforation repair material irrespective of the status of blood contamination. Bone cement can be a viable alternative material for furcation perforation repair compared with MTA.